The Quest to End Modern Slavery: Metaphors in corporate modern slavery statements - Ras, Ilse; Gregoriou, Christiana (Anti-Trafficking Review, 2019)
This paper focuses on the modern slavery statements of three major UK high street retailers who are known for their relatively pro-active approach to the debate on corporate responsibility for ethical trading. Drawing on our earlier research in relation to metaphors in British newspaper reporting of modern slavery and human trafficking since 2000, we explore the metaphors that recur across the statements these companies have published in 2016, 2017 and 2018. These statements were published in accordance with the UK Modern Slavery Act 2015, which requires all commercial organisations operating in the UK, with a turnover greater than GBP 36 million, to publish an annual statement outlining the work done to assess and address (the risk of) modern slavery in their supply chains. We find that the metaphors used in these statements generally fail to acknowledge the agency of those workers affected by modern slavery and labour exploitation in a broader sense, the potential complicity of the retailers in sustaining an exploitative industry, and the underlying socio-economic factors that leave workers vulnerable to exploitation. We conclude that more needs to be done to account for the causes of modern slavery so that retailers can prevent rather than react to it.